Designing a Computer-Based Information System: An "Intermediate" Systems Course. - Wilkinson, Joseph W.; Tracy, John A. (The Accounting Review, 1971)
Abstract This article proposes an approach to a second or intermediate accounting information systems course, presuming that the students have had a broadly oriented introductory course in accounting information systems plus introductory courses in quantitative analysis and statistics, managerial accounting and data processing. These prerequisites should not provide any obstacle to the currently enrolled or future senior and graduate accounting majors for whom the course is primarily designed. The major requirement of this proposed course is to design an overall integrated computer-based information system for a hypothetical business firm that is highly simplified but typical. Students are formed into teams, and each student team concentrates on a major area of the firm that it is assigned. In conclusion, a course involving the design, implementation and evaluation of a computer-based information system is a logical addition to the accounting curriculum. It will help to fit the accountant for his future role in serving the business firms in several ways: by utilizing the computer to show how accounting provides data for a total management information and decision-making system, by integrating in a practical and realistic way many of the concepts and techniques that are taught in the present-day accounting and quantitative analysis curricula, and by building up the knowledge regarding computers and information systems to the level advocated by the recent major studies of education for the accounting profession.